2019
DOI: 10.3390/su11247083
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Land Use/Land Cover Change (LULCC) on Water Resources in a Tropical Catchment in Tanzania under Different Climate Change Scenarios

Abstract: Many parts of sub-Saharan Africa (SSA) are prone to land use and land cover change (LULCC). In many cases, natural systems are converted into agricultural land to feed the growing population. However, despite climate change being a major focus nowadays, the impacts of these conversions on water resources, which are essential for agricultural production, is still often neglected, jeopardizing the sustainability of the socio-ecological system. This study investigates historic land use/land cover (LULC) patterns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
60
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 91 publications
(64 citation statements)
references
References 72 publications
(136 reference statements)
3
60
0
1
Order By: Relevance
“…The objectives of the project were the assessment of wetland contribution to food security and of the sustainability of current wetland uses, as well as the spatio-temporal extrapolation of results through simulation modeling and scenarios. Knowledge of land cover holds quantified and spatially explicit information as an imprint of socio-economic activity in wetland landscapes and can be integrated in hydrological and agricultural modeling [6]. However, such data is particularly scarce in many African regions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The objectives of the project were the assessment of wetland contribution to food security and of the sustainability of current wetland uses, as well as the spatio-temporal extrapolation of results through simulation modeling and scenarios. Knowledge of land cover holds quantified and spatially explicit information as an imprint of socio-economic activity in wetland landscapes and can be integrated in hydrological and agricultural modeling [6]. However, such data is particularly scarce in many African regions.…”
Section: Introductionmentioning
confidence: 99%
“…Attention was put on the Kilombero area again since it became increasingly important for Tanzania's agricultural production. Recent publications focus on hydrological impacts of LULC change within the Kilombero catchment [6,12,13]. They reveal a high dependency of the wetland on baseflow contribution from the enclosing catchment and demonstrate strong impacts of anthropogenic LULC change on water balance components at subcatchment scale.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There exist limited studies [28][29][30][31][32] that have demonstrated the impact of climate and land use change on the hydrological processes in the wetland-catchment nexus in East Africa. Yet, this information is vital to evaluate the possible vulnerability and resilience of these ecosystems to climate change, in particular the impacts of low predictability of precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…The pairwise comparisons of measured and predicted discharges are commonly utilized to assess model performance in calibration and validation periods using numerical performance indicators such as the coefficient of determination (R 2 ), the Nash-Sutcliffe efficiency (NSE), the Kling-Gupta efficiency (KGE), and graphical method [51][52][53][54][55]. Some authors have modified the pairwise comparisons to account for measurement uncertainties [25,56].…”
Section: Introductionmentioning
confidence: 99%